Anatomy of the Lymphatic System and the Lymphosome Concept with Reference to Lymphedema - Suami, Hiroo; Scaglioni, Mario F. (Seminars in Plastic Surgery, 2018)
Precise knowledge of the lymphatic system normal anatomy is essential for understanding what structural changes occur in patients with lymphedema. In this article, the authors first review previous anatomical studies and summarize the general anatomy of the lymphatic system and lymphatic pathways in the upper and lower extremities. Second, they introduce their new anatomical concept, the “lymphosome,” which describes how the lymphatic vessels in a particular region connect to the same subgroup of regional lymph nodes. In addition, they describe the anatomical relationship between the perforating lymphatic vessels and arteries. In the last section, they explain the anatomical changes in the lymphatics after lymph node dissection, with reference to secondary lymphedema.
Keywords: lymph capillary; precollector; lymph collecting vessel; lymphosome; sentinel node